Kajian Retorika Struktur Argumen Karya Tulis Ilmiah Siswa Hasil Ekstrakurikuler Karya Ilmiah Remaja SMA - Eka Darlina; Dian Eka Chandra Wardhana; Ria Ariesta (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
The purpose of this study was to describe the structure of the background arguments for the scientific papers contained in the introduction of KIR extracurricular scientific papers for high school students. The research method uses a qualitative descriptive method. The data collection technique uses documentation techniques that are sourced from extracurricular scientific papers by high school adolescents. Data analysis techniques with the steps of coding, classification, and interpretation. Validity test with member check and discourse expert test. The results showed that the argument structure of students' scientific papers extracurricular activities of high school adolescents was patterned: 1) claim, justifications, and conclusions; 2) claim, justifications, conclusions, and sub-conclusions; 3) claim, sub-claim, justifications, and conclusions; 4) claim, justifications, sub-justifications and conclusions; 5) claim and justification. The structure of the argument in scientific writing is good, although some are incomplete, especially the conclusion that has not been presented. The results of this study are expected to be followed up, especially for the extracurricular trainer of high school adolescent scientific papers to provide understanding to students in writing argument paragraphs using a complete variation of argument patterns, namely claim, justifications, and conclusions.